Avaliação mecânica e histológica de pericárdio bovino descelularizado submetido à pressão - Peruzzo, Angela Maria (2013)
The pericardium is a biological tissue used in the manufacture of various products for medical advices and manufacture of heart valves since the early seventies, however, it still requires further study with regard to the changes that the chemical treatments used to manufacture the valves cause. Several studies show that the tissue often undergoes a process of calcification generated by mechanical stress of opening and closing of the leaflets, damaging the hydrodynamics making valvular replacement necessary. Currently tissue engineering study decellularization process of the bovine pericardium to remove cellular components while preserving the extracellular the matrix (ECM), preserving the integrity of collagen it and can also act as anti-calcification. However, one must know the impact that chemical treatment will bring on the mechanical properties of the tissue, such as tensile strength, strain and elongation percentage. In examined studies, the mechanical tests performed on bovine pericardium decellularized tissue was made without being subjected to a pre-tension which is necessary in most cases for formation of the leaflets during the manufacturing of heart valves. For this reason, a study of the effect on mechanical property that a certain pressure exerts on the pericardium, which passed the decellularization process was made. In parallel it was also made a histological evaluation of the tissue to verify the absence of cells and preservation of collagen fibers in decellularized tissue. Four different groups were prepared for test. The group I was called a control group. In group II, the pericardia were decellularized with the PUC method I. Group III was treated as group I, but under pressure of 240 mmHg. The group IV, the pericardia were decellularized and then subjected to pressure using glutaraldehyde 0.2% and 0.5%. After treatment of the groups, all samples were stained in a solution of blue methylene 0.03% for better visualization of the fibers of the tissue. Then the tissues were cut by laser to obtain the specimens and subjected to tensile test. It was obtained from the test, the tensile strength of the samples, the strain and elongation percentage at break. It is observed that the groups which underwent pressure had a lower tensile strength than those without pressure and on the other hand showed a greater elongation percentage. Thus, it can be verified that the effect of the pressure decreased the thickness of the tissues. The decellularization process has show efficient since it has demonstrated the absence of cells and preservation of collagen fibers after technique.